PERLINDUNGAN HUKUM TERHADAP FILM YANG DI SPOILER MELALUI CHANNEL YOUTUBE DITINJAU DARI UNDANG-UNDANG HAK CIPTA - Muhammad Rifqi Hauzan (2023)
As one of the types of works covered by copyright, film frequently encounters copyright infringement in the form of the dissemination of plot spoilers. Because it published the film footage without the creator's consent, this movie spoiler falls under the definition of piracy. The YouTube channel is one of the mediums that is frequently employed. This is what piques the author's curiosity in learning more about copyright law's protection for movies that are spoilered on YouTube. The purpose of the author's investigation into this phenomenon is to learn more about the policies of YouTube with regard to handling copyright violations of movies that are revealed via the YouTube channel, as well as the role of the government in providing legal protection for movies that are revealed via the Youtube channel under copyright law. Through terms of the research methodology the author employs, it is a normative legal approach based on data gathering through a literature review employing primary and secondary data. The Stature Approach and the Case Approach are the approaches the author uses. The results of this research By giving tools for managing authors' copyrights, Youtube assumes liability in the event of copyright infringement. This will assist artists in permanently removing videos that may be infringing on copyright from their Youtube channel. The Copyright Infringement Elimination Form, Copyright Match Tool, Content Verification Program, and Content ID are some of these features. While this is going on, the government regulates copyright by Law Number 28 of 2014 to give legal protection for filmmakers. The two categories of legal protection are preventive legal protection and repressive legal protection. Article 54 of the Copyright Law, which gives the government the responsibility of regulating the distribution of work that violates copyright, is enforced by the government as preventive legal protectionAdditionally, authors can document their works for use in court. While the repressive legal protection is provided through the courts, arbitration, and other out-of-court dispute settlement processes. The commercial court is where disputes are resolved through the legal system. The Ministry of Communication and Informatics removes content that violates copyright, and the Directorate General of Intellectual Property conducts monitoring, evaluation, and reporting in the area of intellectual property, including copyright, as part of the government's efforts to combat copyright infringement.